What is quantum biology? - Gregory D. Scholes; Graham R. Fleming (Proceedings of the National Academy of Sciences, 2026)
Quantum biology is the field at the intersection of quantum-related physics and the biology of living systems. The goal of the field is to determine if quantum phenomena underpin biological function at the macroscale. Such results, supported by compelling experimental evidence, will be important because they will show how quantum effects can have functional relevance, even in very complex and nominally classical systems. Here, we attempt to define the scope of quantum biology with a forward-facing view to help focus the research agenda. To that end, we propose open questions fundamental to consolidating the field of quantum biology. These open questions highlight the importance of developing suitable probes at the quantum scale, the possibility that classical biological machinery might simply mimic quantum systems, and of elucidating the ways quantum function can be amplified to the macroscale.